Pengaruh Store Image Dan Store Atmosphere Terhadap Impulse Buying Pada Konsumen Dafinna Swalayan Di Tenggarong - Sri Wahyuni; Sugeng Raharjo (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Abstract:The main purpose of this research is to find out the influence of store image and store atmosphereon impulse buying on consumer self-service dafinna in Tenggarong. In this study used multipe regression analysis with equation model. The process of calculating data using manual tools and the distribution of questionnaires.Based onresult of f test it can be concluded that store image and store atmosphere variabels simultan eously have an effect on impulse buying. By using method entered, jika f arithmetic is bigger than f tabel (f count 80,349> f tabel 0,274). Then independent variables have a significant  relationship or impulse buying variables influenced by the variable store image and store atmosphere significantly influence the impulse buying on self-service Dafinna Swalayan in Tenggarong.” Accepted and proven to be true.From the results of partial correlation test seen the value of the largest image store variable than the variable store atmosphere t tabel (T arithmetic 8,964< T table 1,666) So ho rejected and H1 accepted. From the results of the partial test looks the most dominant influence on impulse buying on Dafinna Swalayan in Tenggarong.” Accepted and proven to be true.Keywords : Store Image, Store Atmosphere, Impulse Buying